Similarity in Chronotype and Preferred Time for Sex and Its Role in Relationship Quality and Sexual Satisfaction - Jocz, Paulina; Stolarski, Maciej; Jankowski, Konrad S. (Frontiers in Psychology, 2018)
Recently, the issue of diurnal preferences has been increasingly studied within the context of romantic relationships and sexual functioning. In the present paper we apply a dyadic design to investigate the role of romantic partners’ diurnal preferences in determining a variety of relationship outcomes. A sample of heterosexual couples (N=91) filled a set of questionnaires measuring relationship satisfaction, sexual satisfaction, and morningness-eveningness, and answered questions regarding their actual and preferred time for sexual activity. Conducted analyses revealed that similarity in chronotype between partners and female morningness fostered relationship satisfaction in females, but not in males. Furthermore, morningness-eveningness was associated with preferred time for sex in males, but not in females, who in principle preferred evening hours. Although actual time for sex was up to the female preference, sexual satisfaction in both genders was associated with lower discrepancy in their preferred time for sex and greater frequency of intercourse. In sum, these results indicate that chronotype and time for sex are important factors affecting sexual and relationships satisfaction in heterosexual couples.